Stem cells a novel approach to periodontal regeneration (A review of literature) - Saba S Al-Sarraj; Saif S Saliem (College of Dentistry/ University of Baghdad, 2014)
In this review of literature, the light will be concentrated on the role of stem cells as an approach in periodontal regeneration.